2010
DOI: 10.1038/nmeth.1415
|View full text |Cite
|
Sign up to set email alerts
|

Bright cyan fluorescent protein variants identified by fluorescence lifetime screening

Abstract: Optimization of autofluorescent proteins by intensity-based screening of bacteria does not necessarily identify the brightest variant for eukaryotes. We report a strategy to screen excited state lifetimes, which identified cyan fluorescent proteins with long fluorescence lifetimes (>3.7 ns) and high quantum yields (>0.8). One variant, mTurquoise, was 1.5-fold brighter than mCerulean in mammalian cells and decayed mono-exponentially, making it an excellent fluorescence resonance energy transfer (FRET) donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
252
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(259 citation statements)
references
References 18 publications
7
252
0
Order By: Relevance
“…This reduces calcium buffering caused by the indicator and potential residual biological activity of the sensing domain. Other improvements may arise from incorporating brighter fluorescent protein variants, such as mCerulean3 45 or mTurquoise 46 , to allow lower expression levels while maintaining the same signal-to-noise levels.…”
Section: Discussionmentioning
confidence: 99%
“…This reduces calcium buffering caused by the indicator and potential residual biological activity of the sensing domain. Other improvements may arise from incorporating brighter fluorescent protein variants, such as mCerulean3 45 or mTurquoise 46 , to allow lower expression levels while maintaining the same signal-to-noise levels.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies demonstrating that wavelengths near 800 nm could be used for relatively selective excitation of CFP over YFP 38,39 , we focused our evaluations of potential FRET acceptors on newer, improved variants of YFP. Based on these studies, we identified monomeric (m)Turquoise 35 and mVenus 40 as optimal FPs for TPLSM. We found that illumination at 810 nm efficiently excited mTurquoise with minimal direct excitation of mVenus 33 .…”
Section: Development Of the Protocolmentioning
confidence: 98%
“…Since the cyan FPs (CFP) are optimally excited close to the power maximum of the titanium-sapphire lasers used in most TPLSM systems, we focused our evaluations of potential FRET donors on the newer variants of the CFPs that have improved brightness and photostability, and no photo-switching behavior [34][35][36][37] . Based on previous studies demonstrating that wavelengths near 800 nm could be used for relatively selective excitation of CFP over YFP 38,39 , we focused our evaluations of potential FRET acceptors on newer, improved variants of YFP.…”
Section: Development Of the Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, CFP mutants with a single, long lifetime and increased brightness and photostability (e.g., mTurquoise or mCerulean3) have been developed that are suitable for donor FPs in FRET biosensors, with great potential for in vivo application (48,49). However, there is a paradoxical concern about the application of this pair to two-photon excitation intravital FRET microscopy, mainly due to the proximity of their excitation profiles at relatively short wavelength.…”
Section: Improvement Of Biosensors For Two-photon Intravital Imagingmentioning
confidence: 99%